The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3844/ajbbsp.2016.95.101
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Status of Boar Semen during Storage

Abstract: Abstract:The intensification of the use of artificial insemination in the swine industry has increased the interest to develop proper conditions to store semen better for longer periods of time without affecting its fertility. Trolox is a vitamin E analog with antioxidant property to prevent oxidative stress. Therefore, the objective of this study was to evaluate the Trolox antioxidant capacity on boar semen during storage period (86 h) at 15°C. For that, semen samples from 5 different boars were collected and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
(33 reference statements)
0
5
1
1
Order By: Relevance
“…The sperm motility and vigor reduced throughout the days of observation. However, the addition of vitamin C and Trolox did not differ for progressive motility and vigor compared with the control group in the present study, unlike the results found by Zanella et al (2016), whose study used semen diluted and cooled to 15 o C, and Trolox added at a concentration of 50μM. They found higher values of motility after the first 24 h of storage in samples that contained this antioxidant.…”
Section: Resultscontrasting
confidence: 90%
“…The sperm motility and vigor reduced throughout the days of observation. However, the addition of vitamin C and Trolox did not differ for progressive motility and vigor compared with the control group in the present study, unlike the results found by Zanella et al (2016), whose study used semen diluted and cooled to 15 o C, and Trolox added at a concentration of 50μM. They found higher values of motility after the first 24 h of storage in samples that contained this antioxidant.…”
Section: Resultscontrasting
confidence: 90%
“…Susilawati et al (2014) menyatakan bahwa spermatozoa setelah dilakukan sexing menggunakan metode Sentrifugasi Gradien Densitas Percoll akan mengalami penurunan kualitas disebabkan karena terjadinya kerusakan membran spermatozoa. Proses sentrifugasi menyebabkan terjadinya peningkatan radikal bebas yang disebut dengan Reactive Oxygen Spesies (ROS) hal ini disebabkan oleh adanya kerusakan membran (Zanella et al, 2016). Radikal bebas yang berpengaruh terhadap pengaturan fisiologi sespermatozoa pada saat kapasitasi, dan hiper aktivasi (Aitkel et al, 2012).…”
Section: Persentase Motilitas Dan Motilitas Progresif Setelah Sexing Dan Pendinginanunclassified
“…Susilawati et al (2014) found that centrifugation process might also damage the sperm membrane, thus causing a decrease in sperm motility. The centrifugation process provided free radicals namely Reactive Oxygen Species (ROS) that damaged the sperm membrane (Zanella et al, 2016). ROS are free radicals that play a crucial role in many sperm physiological processes such as capacitating, hyperactivation and spermoocytes fusion (Aitken et al, 2012;Ball, 2008;Bansal and Bilaspuri, 2011).…”
Section: Motility and Abnormality Of Filial Ongole Cattle Sexed Semenmentioning
confidence: 99%